Partition of Unity Finite Element Method for Solving Phase Change Problems - Kayyani, Abdulla Hussain (2023)
A Master of Science thesis in Mathematics by Abdulla Hussain Kayyani entitled, “Partition of Unity Finite Element Method for Solving Phase Change Problems”, submitted in November 2023. Thesis advisor is Dr. Youssef Belhamadia. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).